FACTORS AFFECTING SPEED OF SERVICE WITH WORK ENGAGEMENT AS INTERVENING VARIABLES IN PHARMACEUTICAL INSTALLATIONS - Kurniasih Kurniasih; Mulyati Mulyati; Zuriyati Ulfa; Misan Cahyana; Mintarsi Mintarsi; Rokiah Kusumapradja (Kesatuan Press, 2023)
This research is based on the dynamics of waiting time for drugs in 2021 which are not under regulatory standards. The purpose of this study was to empirically reveal the influence of HRM functions and facilities on the speed of drug waiting time service with work engagement as an intervening variable. The research design used a cross-sectional study and made 50 pharmacy installation officers the unit of analysis. The results of the study prove that the human resources management (HRM) function and facilities have a positive and significant effect on work engagement, the HRM function, facilities and work engagement have a positive and significant effect on the speed of service waiting time for drugs, and work engagement provides a positive intervention on the relationship between HRM functions and facilities on the speed of service time to wait for medicine. Work engagement is a psychological condition in which individuals are fully committed to helping the organization achieve its goals; with work engagement, pharmacy installation officers will try to meet the organization's expectations of speeding up drug waiting times according to applicable standards.